THE LIFE AND PHILOSOPHICAL ACTIVITY OF HAKIM TIRMIZI - Mamadaliyeva Husnora Bahodir qizi (Western European Studies, 2026)
This article examines the life, intellectual legacy, and philosophical activity of Hakim Tirmizi, one of the prominent thinkers of early Islamic civilization. The study analyzes his views on the relationship between reason and revelation, the concepts of heart and knowledge, and the spiritual perfection of the human being. Particular attention is paid to Hakim Tirmizi’s interpretation of wilayah (sainthood) as the highest stage of moral and spiritual development. The article highlights his contribution to the formation of Sufi philosophy and his influence on subsequent Islamic scholars. The research is based on historical, philosophical, and comparative methods.
Keywords: Hakim Tirmizi; Islamic philosophy; Sufism; spiritual knowledge